2007
DOI: 10.1111/j.1740-8784.2007.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Entry into a New Market: An Empirical Study of Taiwanese Firms in China

Abstract: This study examines the determinants of the timing of Taiwanese firms' entry into China. Our empirical findings suggest that this strategic decision is influenced by both economic and institutional concerns. In particular, we found that Taiwanese firms that expected greater benefits from early entry tended to be early entrants in China, while those that were more sensitive to uncertainty chose to defer their entry. We also found a curvilinear relationship between firm size and timing of entry into China. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 94 publications
(169 reference statements)
0
16
0
Order By: Relevance
“…However, few previous studies have applied survival analysis to investigate FDI survival duration for foreign affiliates. Lin et al (2009) andTan et al (2007) applied survival analysis to investigate FDI. Lin et al (2009) used survival analysis to examine the relationship between Taiwanese foreign investment behavior and duration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few previous studies have applied survival analysis to investigate FDI survival duration for foreign affiliates. Lin et al (2009) andTan et al (2007) applied survival analysis to investigate FDI. Lin et al (2009) used survival analysis to examine the relationship between Taiwanese foreign investment behavior and duration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…the probability of early foreign investment increased). Tan et al (2007) used the Cox proportional hazards model to analyze the points in time at which Taiwanese businesses planned to enter China, and suggested that these decisions are influenced by both the Taiwanese and the Chinese economies and systems. The results indicated that a U-shaped relationship, rather than a linear one, exists between business scales and time points for entering the Chinese market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 45 first authors in the three volumes of MOR , only ten are from the Greater China region, less than 25 percent. Four are from mainland China (Lu et al., 2006; Luo, 2005; Xiao and Bjorkman, 2006; Zhang et al., 2006), three from Hong Kong (Choi and Chen, 2006; Huang et al., 2005; Tjosvold et al., 2006), one from Taiwan (Tan et al., 2007), and two from Singapore (Ang et al., 2007; Ng and Chua, 2006). Of the four authors from mainland China, three obtained their research training from outside the mainland.…”
Section: Looking Aheadmentioning
confidence: 99%
“…The same characteristics that help firms to benefit from early entry may also provide them with the organisational slack to defer entry decisions until market uncertainty is resolved. To understand how these firm characteristics influence entry timing requires a comparison of the effect of firm resources in regard to early entry versus deferred entry (Tan, Hung, & Liu, 2007).…”
Section: Introductionmentioning
confidence: 99%